1984
DOI: 10.1139/v84-071
|View full text |Cite
|
Sign up to set email alerts
|

Surface photochemistry: generation of benzyl radical pairs on dry silica gel

Abstract: . 62, 403 (1984).Singlet and triplet benzyl radical pairs have been generated on silica gel by photolysis of a benzyl phenylacetate, a dibenzyl ketone, and a dibenzyl sulfone. The extent of geminate radical recombination has been measured and requires that translational motion of radicals occur on the silica gel surface. This motion was affected by the radical pair multiplicity and the photolysis temperature, but was relatively insensitive to the state of hydration of the silica gel and the presence of coadsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…For example, on silica, benzyl radicals generated from a triplet precursor recombine with product ratios that are very close to the statistical ratio obtained in solution, leading to cage effects of -0 (35). Similar radicals generated as a singlet pair show a cage effect of 40% (36). The predominance of ketone 8a, which corresponds to ortho coupling of the two radicals, is also indicative of restricted mobility of the radicals.…”
Section: Discussionmentioning
confidence: 95%
“…For example, on silica, benzyl radicals generated from a triplet precursor recombine with product ratios that are very close to the statistical ratio obtained in solution, leading to cage effects of -0 (35). Similar radicals generated as a singlet pair show a cage effect of 40% (36). The predominance of ketone 8a, which corresponds to ortho coupling of the two radicals, is also indicative of restricted mobility of the radicals.…”
Section: Discussionmentioning
confidence: 95%
“…When dibenzyl ketone is photolysed in either micelles (6) or on silica gel (18), an isomeric product, 1-phenyl-4'-methylacetophenone, 2, is produced. This isomer is formed by geminate recombination of the initial radical pair and is thus expected to be formed more often from I3C ketone molecules than from "C molecules.…”
Section: Discussionmentioning
confidence: 99%
“…When the ketone was to be adsorbed on silica gel dried at 200°C at I Torr for ? 5 h. the previously described method and apparatus were used (18). For samples on silica gel which had not been predried, a methylene chloride solution of I was added to a preweighed silica sample in a round bottom flask.…”
Section: Methodsmentioning
confidence: 99%
“…In many cases it has been demonstrated that adsorption on solids such as silica and alumina and inclusion in zeolites can often modify the normal solution photochemistry of a given species. In particular, a variety of benzyl radical pairs have been used to examine the effects of zeolites and silicas on the pathways available to organic molecules adsorbed on the various surfaces (1,2,4). These studies have investigated the effects of the additives, temperature, and modifications of the silica or zeolite properties upon the observed chemistry of the radicals.…”
mentioning
confidence: 99%